Trans-Resveratrol ameliorates anxiety-like behaviors and neuropathic pain in mouse model of post-traumatic stress disorder. (July 2020) - Yuan, Yirong; Zhen, Linlin; Li, Zhi; Xu, Wenhua; Leng, Huilin; Xu, Wen; Zheng, Victor; Luria, Victor; Pan, Jianchun; Tao, Yuanxiang; Zhang, Hanting; Cao, Shengsheng; et al.
Background: trans -Resveratrol has been extensively investigated for its anti-inflammatory, antioxidant, and anti-psychiatric properties. However, whether it could rescue posttraumatic stress disorder-like stress-induced pain abnormality is unknown. Aim: The present study examined the effects of trans -resveratrol on anxiety-like behavior and neuropathic pain induced by single-prolonged stress, which is a classical animal model for mimicking posttraumatic stress disorder. Methods: The single-prolonged stress-induced anxiety-like behavior and pain response were detected by the novelty suppressed feeding, marble burying, locomotor activity, von Frey, and acetone-induced cold allodynia tests in mice. The serum corticosterone levels and glucocorticoid receptor, protein kinase A, phosphorylated cAMP response element binding protein, and brain-derived neurotrophic factor expression were detected by enzyme-linked immunosorbent assay and immunoblot analyses. Results: trans -Resveratrol reversed single-prolonged stress-induced increased latency to feed and the number of marbles buried in the novelty suppressed feeding and marble burying tests, but did not significantly influence locomotion distance in the locomotor activity test. trans -Resveratrol also reversed single-prolonged stress-induced cold and mechanical allodynia. Moreover, single-prolonged stress induced abnormality in the limbic hypothalamus-pituitary-adrenal axis was reversed by trans -resveratrol, as evidenced by the fact that trans -resveratrol reversed the differential expression of glucocorticoid receptor in the anxiety- and pain-related regions. In addition, trans -resveratrol increased protein kinase A, phosphorylated cAMP response element binding protein, and brain-derived neurotrophic factor levels, which were decreased in mice subjected to single-prolonged stress. Conclusions: These results provide compelling evidence that trans -resveratrol protects neurons against posttraumatic stress disorder-like stress insults through regulation of limbic hypothalamus-pituitary-adrenal axis function and activation of downstream neuroprotective molecules such as protein kinase A, phosphorylated cAMP response element binding protein, and brain-derived neurotrophic factor expression.